Analysis of the calorific value of pellets and briquettes in the use of the pseudostem of Banana (Musa paradisiaca) - Peña Murillo, Sandra Emperatriz; Zambrano Nevárez, Eddie Manuel; Fajardo Muñoz, Sandra Elvira; Pérez Ortiz, Nahir Alondra; Vaca Choez, Darla Rosario; Fajardo Echeverri, Pablo (Ingeniería Química y Desarrollo, 2025)
Solid biofuels belong to the second generation according to the type of biomass obtained from agricultural, forestry, and industrial wastes, such as banana pseudostem, which is a lignocellulosic biomass that can be used as an alternative for the generation of renewable energy in the form of pellets and briquettes due to its energetic properties. The study aims to determine the calorific value efficiency of solid biofuels based on Plantain (Musa paradisiaca) pseudostem. The study methodology was divided into three parts: (1) obtaining and conditioning of biomass, (2) elaboration of solid biofuels, and (3) physical, proximal, and energy potential analysis of biomass and the respective ANOVA of pellets and briquettes. A high calorific value was found for the compositions 55-45% in pellet with 22,657 MJ/kg and 50-50% in briquette with 22,680 MJ/kg, complying with the parameters established in the ENplus and NTC 2060 standards, respectively.
Keywords: Pseudostem; Biomass; Calorific value; Pellet; Briquette